The crisis of the Spanish economy - Juan F. Jimeno; Tano Santos (SERIEs - Journal of the Spanish Economic Association, 2014)
This article offers a narrative of the Spanish crisis building upon previous literature and the papers published in this issue. This narrative focuses on two main topics: (1) the reasons why the Spanish economy embarked in the expansionary/speculative path resulting in an over-accumulation of debt and severe macroeconomic imbalances that led to the crisis, and (2) the factors that explain why the Spanish crisis materialized with such a high intensity and duration. The article addresses them by highlighting three main characteristics of the Spanish economy in the pre-crisis period: (1) a composition of economic activity increasingly biased towards construction, real state, and other non-tradeable sectors, (2) a banking system that was able to satisfy the huge increase in credit demand arising from households and firms, in a context of very low real interest rates, excessive optimism about growth, and large facilities for using real assets as loan collateral, and (3) the recourse to external funding that originated an unprecedented increase in liabilities with respect to the rest of the world.
Keywords: E30; F40; G01; 330; Spanish crisis; Productive model; External imbalances; Financial sector